A method of regulating alkali metal fluoride crystal growth in a solid-state electrolyte interface
Patent Information
- Application Number
- CN202611494098.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-23
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]目前关于富LiF SEI的研究仍主要聚焦于“形成多少LiF”和“LiF分布在哪里”,针对电池工作状态下LiF晶体尺寸如何形成、如何通过电解液组分直接调控其成核/生长及溶解-再结晶过程的技术方案相对不足
[0014]本发明可以在不改变含硼添加剂进攻增溶基本机理的情况下,利用分子空间位阻作为可调结构参数对LiF晶体尺寸进行控制,从而为固态电解质界面中LiF由大尺寸晶体向小尺寸、分散型晶体转变提供一种可操作的电解液添加剂调控方法。
Smart Images

Figure CN122992175A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for growing alkali metal fluoride crystals. Background Technology
[0002] The solid electrolyte interface (SEI) is a crucial interfacial layer formed between the electrolyte and electrodes in lithium-ion secondary batteries. It needs to both block electrons to inhibit the continuous decomposition of the electrolyte and allow lithium ions to pass through. Therefore, its composition, microstructure, and stability directly affect the battery's capacity, cycle life, rate performance, and safety. Lithium fluoride (LiF) is widely considered a key inorganic component in the SEI due to its wide electrochemical window, high mechanical strength, and high surface energy. Existing technologies typically increase the LiF content in the SEI by employing fluorinated lithium salts, fluorinated solvents, or fluorinated additives to obtain a LiF-rich interface.
[0003] However, simply increasing the LiF content cannot fully solve the interfacial ion transport problem. Bulk or large-sized LiF has low intrinsic ion / electron conductivity, and when it exists in the SEI as large grains or continuous dense regions, it easily forms local resistivity barriers. Conversely, small-sized, discretely distributed LiF can shorten the effective transport distance of ions across the inorganic phase and increase the number of grain boundaries and phase interfaces, thus being more conducive to interfacial ion migration. Existing materials further show that as the LiF crystal size decreases, its X-ray diffraction peak intensity decreases and the peak width broadens, indicating changes in crystallinity and crystal system, suggesting that the LiF size itself is an important structural parameter affecting its interfacial behavior.
[0004] Current research on LiF-rich SEIs mainly focuses on "how much LiF is formed" and "where LiF is distributed." There is a relative lack of technical solutions addressing how LiF crystals are formed under battery operating conditions and how to directly control their nucleation / growth and dissolution-recrystallization processes through electrolyte components. In particular, there is a lack of a method that can be directly introduced as an electrolyte additive, is compatible with existing lithium battery systems, and utilizes specific chemical interactions to attack and solubilize LiF, thereby controlling larger LiF crystals into nanoscale, small-sized, and dispersed structures during SEI formation. Summary of the Invention
[0005] The purpose of this invention is to provide a method for regulating the growth of alkali metal fluoride crystals at the solid electrolyte interface.
[0006] The method for regulating the growth of alkali metal fluoride crystals at the solid electrolyte interface of the present invention involves adding a boron-containing additive to a lithium battery electrolyte containing a LiF component; wherein the boron-containing additive is one or more of tris(2,4,6-trifluorophenyl)borane (2,4,6-TTFPB), tris(3,4,5-trifluorophenyl)borane (3,4,5-TTFPB), and triphenylborane (TPB).
[0007] Furthermore, the amount of boron-containing additive added is 0.5% to 1.5% of the mass of the lithium battery electrolyte containing LiF components. The specific amount of boron-containing additive added to the base electrolyte can be adjusted according to its solubility, electrochemical compatibility, and target LiF particle size. Preferably, by controlling the type and amount of additive, the resulting electrolyte forms an SEI containing LiF crystals of different sizes during battery formation.
[0008] Furthermore, lithium battery electrolytes that can form LiF components are electrolytes containing LiPF6, LiFSI, or LiTFSI.
[0009] Furthermore, the lithium battery electrolyte that can form the LiF component is formed by adding LiPF6 to a mixed solvent at a concentration of 1 M; wherein the mixed solvent is obtained by mixing EC, EMC and DMC uniformly at a volume ratio of ethylene carbonate (EC): ethyl methyl carbonate (EMC): dimethyl carbonate (DMC) of 1:1:1.
[0010] All three boron-containing additives of this invention possess boron-containing centers capable of interacting with fluorine (F) on the LiF surface. However, due to differences in the fluorine substitution positions, linkage modes, and overall molecular configurations on the aromatic rings, the areas surrounding the boron centers and the outer layers of the molecule exhibit varying steric environments. This steric hindrance affects, on the one hand, the geometrical accessibility of the boron-containing centers to the LiF surface, and on the other hand, it influences the re-nucleation, growth, particle contact, and coalescence processes of LiF after local dissolution, thus producing differentiated crystal size control effects. This invention utilizes the strong affinity / coordination ability of boron-containing compounds for fluorine to intervene in the dissolution and recrystallization processes of the LiF surface, achieving controllable adjustment of the LiF crystal size and dispersion state without altering the basic battery configuration.
[0011] The regulation process of the boron-containing additive of the present invention includes: First, the boron-containing sites, acting as Lewis acid centers, coordinate / bond with F on the LiF surface, forming stable BF interactions, weakening the Li-F interactions on the LiF lattice surface and promoting the entry of LiF surface species into the liquid phase, thereby achieving attack and solubilization of LiF; Second, the locally dissolved Li... +First, fluorine-containing species re-nucleate and recrystallize under the influence of interfacial concentration fields and electrochemical reactions, gradually refining the original large-sized crystals. Second, the steric hindrance environment of different additives restricts the continued growth and particle aggregation of LiF after recrystallization to varying degrees, thus obtaining LiF with different grain sizes and dispersion states. A schematic diagram illustrating the mechanism by which boron-containing additives attack and solubilize LiF and regulate crystal size is shown below. Figure 1 As shown.
[0012] In this invention, 2,4,6-TTFPB and 3,4,5-TTFPB are structural isomers of triarylboranes with different substitution positions, which can be used to compare the differences in local steric hindrance caused by changes in the fluorine substitution position; TPB does not contain fluorine substituents in the aromatic ring and can be used as another triarylborane structural reference. By constructing different steric hindrance environments using the above three regulators, the gradient regulation of LiF crystal size can be achieved while maintaining the basic mechanism of attack solubilization.
[0013] Compared to systems without crystallization-regulating additives, this invention utilizes 2,4,6-TTFPB, 3,4,5-TTFPB, and TPB to attack and solubilize LiF, inducing dissolution and recrystallization, which can directly alter the size and dispersion state of LiF crystals in the SEI. The three regulators share the same basic boron-containing attack and solubilization function, but their different steric environments restrict LiF surface dissolution, re-nucleation, continued grain growth, and particle aggregation to varying degrees, thus achieving differentiated LiF size regulation effects.
[0014] This invention can control the size of LiF crystals by using molecular steric hindrance as an adjustable structural parameter without changing the basic mechanism of boron-containing additives to attack and solubilize. This provides an operable method for regulating electrolyte additives to transform LiF from large-sized crystals to small-sized, dispersed crystals in solid electrolyte interfaces. Attached Figure Description
[0015] Figure 1 This is a schematic diagram illustrating the mechanism of attack, solubilization, and size control of LiF crystals by the boron-containing additive of this invention.
[0016] Figure 2 The image shows the SEM morphology of the original LiF after immersion in a basic electrolyte without boron-containing regulator for 12 h.
[0017] Figure 3 The image shows the SEM morphology of the original LiF after immersion in an electrolyte containing 1 vol% 2,4,6-TTFPB for 12 h.
[0018] Figure 4 The image shows the TEM morphology of the original LiF after immersion in an electrolyte containing 1 vol% 2,4,6-TTFPB for 12 h.
[0019] Figure 5 The XRD patterns are of the original LiF samples obtained after reacting for 12 h in the basic electrolyte of Comparative Example 1 and the electrolyte containing 1 vol% 2,4,6-TTFPB in Example 1.
[0020] Figure 6 The graph shows the ionic conductivity test results of the original LiF.
[0021] Figure 7 The graph shows the ionic conductivity test results of the original LiF after immersion in an electrolyte containing 1 vol% 2,4,6-TTFPB for 12 h.
[0022] Figure 8 The graph shows the electronic conductivity test results of the original LiF.
[0023] Figure 9 The graph shows the electronic conductivity test results of the original LiF after immersion in an electrolyte containing 1 vol% 2,4,6-TTFPB for 12 h.
[0024] Figure 10 The graphs show the cycle performance of Li-Gr half-cells prepared with the lithium battery electrolytes obtained in Example 1 and Comparative Example 1, respectively.
[0025] Figure 11 Rate curves of Li-Gr half-cells prepared with the lithium battery electrolytes obtained in Example 1 and Comparative Example 1, respectively.
[0026] Figure 12 The image shows the SEM morphology of the original LiF after immersion in an electrolyte containing 3,4,5-TTFPB for 12 h.
[0027] Figure 13 The image shows the TEM morphology of the original LiF after immersion in an electrolyte containing 3,4,5-TTFPB for 12 h.
[0028] Figure 14 The XRD patterns are of the original LiF samples obtained after reacting for 12 h in the basic electrolyte of Comparative Example 1 and the electrolyte containing 1 vol% 3,4,5-TTFPB in Example 5.
[0029] Figure 15 The graph shows the ionic conductivity test results of the original LiF after immersion in an electrolyte containing 1 vol% 3,4,5-TTFPB for 12 h.
[0030] Figure 16The graph shows the electronic conductivity test results of the original LiF after immersion in an electrolyte containing 1 vol% 3,4,5-TTFPB for 12 h.
[0031] Figure 17 The graphs show the cycle performance of Li-Gr half-cells prepared with the lithium battery electrolytes obtained in Example 5 and Comparative Example 1, respectively.
[0032] Figure 18 Rate curves of Li-Gr half-cells prepared with the lithium battery electrolytes obtained in Example 5 and Comparative Example 1, respectively.
[0033] Figure 19 The image shows the SEM morphology of the original LiF after immersion in an electrolyte containing 1 vol% TPB for 12 h.
[0034] Figure 20 The image shows the TEM morphology of the original LiF after immersion in an electrolyte containing 1 vol% TPB for 12 h.
[0035] Figure 21 The XRD patterns are of the original LiF samples obtained after reacting for 12 h in the basic electrolyte of Comparative Example 1 and the electrolyte containing 1 vol% TPB in Example 6.
[0036] Figure 22 The graph shows the ionic conductivity test results of the original LiF after immersion in an electrolyte containing 1 vol% TPB for 12 h.
[0037] Figure 23 The graph shows the electronic conductivity test results of the original LiF after immersion in an electrolyte containing 1 vol% TPB for 12 h.
[0038] Figure 24 The graphs show the cycle performance of Li-Gr half-cells prepared with the lithium battery electrolytes obtained in Example 6 and Comparative Example 1, respectively.
[0039] Figure 25 Rate curves of Li-Gr half-cells prepared with the lithium battery electrolytes obtained in Example 6 and Comparative Example 1, respectively. Detailed Implementation
[0040] The beneficial effects of the present invention will be verified using the following examples.
[0041] Example 1: The method for controlling the growth of alkali metal fluoride crystals at the solid electrolyte interface in this example involves adding a boron-containing additive, tris(2,4,6-trifluorophenyl)borane (2,4,6-TTFPB), to a lithium battery electrolyte containing a component capable of forming LiF. Details are as follows:
[0042] 1. Mix EC, EMC and DMC evenly in a volume ratio of 1:1:1 to obtain a mixed solvent; then add LiPF6 to the mixed solvent at a concentration of 1 M, stir and mix evenly to obtain the basic electrolyte.
[0043] 2. Add 1% by volume of tris(2,4,6-trifluorophenyl)borane (2,4,6-TTFPB) to the base electrolyte and mix until a homogeneous solution is formed to obtain the lithium battery electrolyte.
[0044] Comparative Example 1: No boron-containing regulator was added to this comparative example. The preparation method of the lithium battery electrolyte in this comparative example is as follows: EC, EMC and DMC are mixed evenly in a volume ratio of ethylene carbonate (EC): ethyl methyl carbonate (EMC): dimethyl carbonate (DMC) of 1:1:1 to obtain a mixed solvent; then, LiPF6 is added to the mixed solvent at a concentration of 1 M and stirred evenly to obtain the lithium battery electrolyte used as a comparison.
[0045] To directly verify the attack, solubilization, and size regulation effects of boron-containing regulators on LiF crystals, an in-situ model experiment was conducted using pristine LiF. 0.5 mmol of pristine LiF with a particle size of 1–2 μm was added to 2 mL of the lithium battery electrolyte containing 2,4,6-TTFPB obtained in Example 1 and 2 mL of the basic electrolyte without boron-containing regulators obtained in Comparative Example 1, respectively. The solutions were allowed to stand and react for 12 h under the same conditions. After the reaction, the LiF solid was separated, and the resulting LiF was characterized by SEM and TEM.
[0046] Figure 2 The image shows the SEM morphology of the original LiF after immersion in the basic electrolyte (without boron-containing modifier) obtained in Comparative Example 1 for 12 h. Figure 2 It can be seen that, without the presence of boron-containing regulators, LiF mainly maintains regular large-sized block crystals with clear crystal boundaries, relatively smooth surfaces, and single particle sizes reaching the micrometer level. This indicates that the basic electrolyte itself has little influence on the morphology and size of the original LiF crystals during this reaction time.
[0047] Figure 3 The image shows the SEM morphology of the original LiF after immersion in the electrolyte containing 2,4,6-TTFPB obtained in Example 1 for 12 h. Figure 3It can be seen that after 12 h of treatment with 2,4,6-TTFPB, the original micron-sized regular blocky structure of the original LiF basically disappeared, and the sample was mainly composed of a large number of fine particles, forming a relatively loose particle aggregate. The LiF crystal size was approximately 15-20 nm. Compared with Comparative Example 1, 2,4,6-TTFPB significantly refined the original LiF, indicating that it can directly act on the LiF crystal and produce an attack-soliciting effect. The fluorine substitution at the 2, 4, and 6 positions of the aromatic ring in the 2,4,6-TTFPB molecule creates a specific near-end steric environment around the boron-containing center, which, while promoting the dissolution of the LiF surface, restricts subsequent recrystallization, continued grain growth, and particle aggregation. Figure 4 The TEM images of the LiF samples show that the LiF treated with 2,4,6-TTFPB consists of numerous dispersed nanoparticles, with primary particles mainly in the tens of nanometers range, and no complete micron-sized bulk crystals observed. The TEM results are consistent with the SEM results, further demonstrating that 2,4,6-TTFPB can significantly refine the original large-sized LiF into nanoscale particles through attack-induced solubilization and control of the recrystallization process. This result provides experimental modeling evidence for controlling the LiF crystal size within the SEI in battery systems.
[0048] Figure 5 The images show the XRD patterns of the original LiF samples obtained after reacting for 12 h in the basic electrolyte of Comparative Example 1 and the electrolyte containing 2,4,6-TTFPB in Example 1. Figure 5 It can be seen that the sample treated with 2,4,6-TTFPB in Example 1 still retains the characteristic diffraction peaks of LiF (111), (200), (220), (311), and (222) at approximately 38°, 44°, 66°, 79°, and 83°, indicating that the basic crystal structure of LiF has not changed. Compared with Comparative Example 1 without the addition of a boron-containing modifier, the intensity of each characteristic peak in Example 1 is significantly reduced and broadened, especially the (111), (200), and (220) peaks, which show significant broadening. This indicates that the grain size is significantly reduced and the long-range order is decreased, which is consistent with the nanostructuring results observed by SEM and TEM.
[0049] 0.5 mmol of pristine LiF particles with a diameter of 1–2 μm were added to 2 mL of the lithium battery electrolyte containing 2,4,6-TTFPB obtained in Example 1 and 2 mL of the basic electrolyte without boron-containing regulator obtained in Comparative Example 1, respectively. The solutions were allowed to stand and react at 25°C for 12 h. After the reaction, the LiF was centrifuged, dried, and pressed into sheets. The ionic conductivity of the LiF sheets was then tested. The ionic conductivity test results of the LiF sheets treated with the lithium battery electrolyte of Comparative Example 1 are shown below. Figure 6 As shown, from Figure 6As can be seen, after treatment with the lithium battery electrolyte of Comparative Example 1, the ionic conductivity of the LiF sheet is only 5.95 × 10⁻⁶. -11 S cm -1 This indicates that large-size, highly crystalline LiF sheets exhibit extremely low intrinsic ion conductivity. This result demonstrates that large-size, highly crystalline LiF sheets tend to form significant ion transport resistance. The ion conductivity test results of the LiF sheets treated with the lithium-ion battery electrolyte in Example 1 are as follows: Figure 7 As shown. By Figure 7 It can be seen that the ionic conductivity of LiF reaches 1.19 × 10⁻⁶ after regulation by 2,4,6-TTFPB. -6 S cm -1 Compared to LiF without the added regulator, which has a viscosity of 5.95 × 10⁻⁶, this figure is significantly lower. -11 S cm -1 The improvement was approximately five orders of magnitude. Combined with morphological and XRD results, the ion transport capability of LiF was significantly improved after grain refinement, indicating that the size regulation of LiF by 2,4,6-TTFPB is beneficial for reducing Li... + Transport resistance through the LiF phase.
[0050] 0.5 mmol of pristine LiF particles with a diameter of 1–2 μm were added to 2 mL of the lithium battery electrolyte containing 2,4,6-TTFPB obtained in Example 1 and 2 mL of the basic electrolyte without boron-containing regulator obtained in Comparative Example 1, respectively. The solutions were allowed to stand and react at 25°C for 12 h. After the reaction, the LiF was centrifuged, dried, pressed into sheets, and the electronic conductivity of the LiF sheets was tested. The electronic conductivity test results of the LiF sheets treated with the lithium battery electrolyte of Comparative Example 1 are as follows: Figure 8 As shown, from Figure 8 It can be seen that during the 3000 s test, the current of the additive-free LiF remained slightly fluctuating around zero, exhibiting near-complete electronic insulation. This result demonstrates that LiF possesses excellent electronic blocking capabilities and can serve as a benchmark for comparing whether various control systems maintain electronic insulation after grain refinement. The electronic conductivity test results of the LiF sheet treated with the lithium battery electrolyte in Example 1 are as follows: Figure 9 As shown, by Figure 9 It can be seen that the electronic conductivity of LiF after modulation by 2,4,6-TTFPB is 9.872 × 10⁻⁶. -9 S cm -1 It is still at 10 -9 S cm -1 The order-of-magnitude low electronic conductivity indicates that while the LiF crystals are significantly refined and their ionic conductivity is improved, their electronic insulation properties are still maintained. This is beneficial for LiF to maintain its role in blocking electron transport and inhibiting the continuous decomposition of the electrolyte at the solid electrolyte interface.
[0051] The lithium-ion battery electrolytes obtained in Example 1 and Comparative Example 1 were used in Li-Gr half-cells, respectively. After standing for 8 hours, they were activated at 0.1 C for 3 cycles. Then, they were cycled at 1 C. The cycling performance of the Li-Gr half-cells is as follows: Figure 10 As shown, from Figure 10 It can be seen that the battery containing 2,4,6-TTFPB electrolyte in Example 1 consistently exhibits a higher discharge specific capacity than the electrolyte in Comparative Example 1 during cycling, with the capacity stabilizing at approximately 360–370 mAh g⁻¹ in the early stages. -1 It can still maintain about 340 mAh g after 500 cycles. -1 The comparative example 1 decreased to approximately 260 mAh g. -1 Meanwhile, the coulombic efficiency remained stable at nearly 100% over a long period. These results indicate that the small-sized LiF formed through 2,4,6-TTFPB regulation can effectively improve interfacial stability and long-cycle capacity retention.
[0052] Li-Gr half-cells were prepared using the lithium battery electrolytes of Example 1 and Comparative Example 1. After standing for 8 hours, they were activated at 0.1 C for 3 cycles, and then their rate performance was tested. The rate curves obtained are shown in the figure. Figure 11 As shown, from Figure 11 As can be seen, when the rate is increased sequentially from 0.1C to 0.2C, 0.5C, 1C, 2C, and 5C, the discharge specific capacity of the Li-Gr half-cell prepared with the electrolyte of Example 1 is generally higher than that of Comparative Example 1, especially at high rates of 2C and 5C, it can still maintain approximately 320 mAh g⁻¹. -1 and 190 mAh g -1 In contrast, the Li-Gr half-cell of Comparative Example 1 has a capacity of only about 160 mAh g. -1 and 60 mAh g -1 After the rate of return is restored to 0.1C, the capacity can be restored to approximately 360 mAh g. -1 This demonstrates that the small-sized LiF obtained by 2,4,6-TTFPB regulation in Example 1 can significantly improve interfacial ion transport kinetics and high-rate performance.
[0053] In summary, 2,4,6-TTFPB in Example 1 significantly refined LiF from micron-sized bulk crystals into nanoparticles, accompanied by a marked broadening of XRD peaks and an increase in ionic conductivity to 10. -6 S cm -1 Orders of magnitude, while the electronic conductivity remains at 10. -9 S cm -1 The improved insulation level, and further enhanced long-cycle and rate performance, indicates that its steric environment can effectively suppress grain growth and particle aggregation after LiF recrystallization.
[0054] Example 2: This example differs from Example 1 in that the amount of 2,4,6-TTFPB added in step two is 0.5% by volume. All other steps and parameters are the same as in Example 1.
[0055] Example 3: This example differs from Example 1 in that the amount of 2,4,6-TTFPB added in step two is 0.8% by volume. All other steps and parameters are the same as in Example 1.
[0056] Example 4: This example differs from Example 1 in that the amount of 2,4,6-TTFPB added in step two is 1.5% by volume. All other steps and parameters are the same as in Example 1.
[0057] 0.5 mmol of pristine LiF with a particle size of 1–2 μm was added to 2 mL of the lithium battery electrolytes containing 2,4,6-TTFPB obtained in Examples 2, 3, and 4, respectively. The solutions were allowed to stand and react for 12 h at 25 °C. The LiF was then separated by centrifugation, dried, and pressed into sheets for ionic conductivity testing. The ionic conductivity results are shown in Table 1.
[0058] Table 1. Ionic conductivity of lithium fluoride after electrolyte treatment in Examples 1-4 and Comparative Example 1
[0059] Example number <![CDATA[Ionic conductivity of lithium fluoride (S cm -1 )]]> Example 2 <![CDATA[1.06×10 -7 ]]> Example 3 <![CDATA[2.80×10 -7 ]]> Example 4 <![CDATA[1.98×10 -7 ]]> Example 1 <![CDATA[1.19×10 -6 ]]> Comparative Example 1 <![CDATA[5.95×10 -11 ]]>
[0060] As shown in Table 1, adding 0.5% to 1.5% of 2,4,6-TTFPB to the electrolyte by volume percentage can significantly improve the ionic conductivity of the original lithium fluoride.
[0061] Example 5: The method for controlling the growth of alkali metal fluoride crystals at the solid electrolyte interface in this example involves adding a boron-containing additive, tris(3,4,5-trifluorophenyl)borane (3,4,5-TTFPB), to a lithium battery electrolyte containing a component capable of forming LiF. Details are as follows:
[0062] 1. Mix ethylene carbonate (EC): ethyl methyl carbonate (EMC): dimethyl carbonate (DMC) in a volume ratio of 1:1:1 to obtain a mixed solvent; then add LiPF6 to the mixed solvent at a concentration of 1 M, stir and mix thoroughly to obtain the basic electrolyte.
[0063] 2. Add 1% by volume of tris(3,4,5-trifluorophenyl)borane (3,4,5-TTFPB) to the base electrolyte and mix until a homogeneous solution is formed to obtain the lithium battery electrolyte.
[0064] To verify the direct size regulation effect of 3,4,5-TTFPB on LiF crystals, 0.5 mmol of pristine LiF with a particle size of 1-2 μm was added to 2 mL of the lithium battery electrolyte containing 3,4,5-TTFPB obtained in Example 5. The mixture was allowed to stand and react at 25°C for 12 h. After the reaction, the LiF solid was separated and its morphology was characterized by SEM and TEM. The 3,4,5-TTFPB in this example has the same number of trifluorine substitutions as the 2,4,6-TTFPB in Example 1, but the fluorine substitution positions are different, thus forming different local spatial environments at the B-center. These can be used to compare the effects of steric hindrance differences on LiF attack solubilization, recrystallization, and final crystal size. Figure 12 As shown, after 12 h of treatment with 3,4,5-TTFPB, the original LiF changed from a micron-sized regular block structure to a large number of fine particles. The particles were at the nanoscale and had good dispersibility. The LiF crystal size was about 45~50 nm. This indicates that 3,4,5-TTFPB can directly promote the refinement of the original LiF and limit its recrystallization and continued growth. Figure 13 The TEM images of the LiF samples show that the LiF treated with 3,4,5-TTFPB consists of relatively dispersed nanoparticles, with primary particles mostly tens of nanometers in size and relatively clear particle boundaries. The TEM results are consistent with the SEM results, further demonstrating that 3,4,5-TTFPB can effectively control the grain size of LiF. Both the SEM and TEM images are non-in-situ model characterizations of the original LiF after reacting with an electrolyte containing additives for 12 h, rather than morphology images obtained directly from the battery bulk phase or SEI.
[0065] Figure 14 The XRD pattern of the original LiF sample obtained after reacting in the electrolyte containing 3,4,5-TTFPB in Example 5 for 12 h shows that the sample regulated by 3,4,5-TTFPB still retains the characteristic diffraction peaks (111), (200), (220), (311), and (222) of LiF, indicating that the phase composition has not changed significantly. Compared with LiF without the added regulator, the characteristic peak intensities of the sample in Example 5 are significantly reduced and broadened, indicating that the LiF grain size is reduced; however, the peak shape is still relatively clear, indicating that the obtained LiF still maintains a certain degree of crystallinity. This result is consistent with the nanoparticle morphology observed by SEM and TEM.
[0066] 0.5 mmol of pristine LiF with a particle size of 1-2 μm was added to 2 mL of the lithium battery electrolyte containing 3,4,5-TTFPB obtained in Example 5. The electrolyte was allowed to stand and react at 25°C for 12 h. The LiF was then separated by centrifugation, dried, and pressed into sheets for ionic conductivity testing. The resulting ionic conductivity graph is shown below. Figure 15As shown, by Figure 15 It can be seen that the ionic conductivity of LiF after regulation by 3,4,5-TTFPB is 1.01 × 10⁻⁶. -6 S cm -1 Compared to the unregulated LiF, which is 5.95 × 10⁻⁶, -11 S cm -1 This represents an improvement of approximately five orders of magnitude. This demonstrates that modulating LiF to the nanoscale using 3,4,5-TTFPB can significantly improve the ion transport capacity of LiF.
[0067] 0.5 mmol of pristine LiF with a particle size of 1-2 μm was added to 2 mL of the lithium battery electrolyte containing 3,4,5-TTFPB obtained in Example 5. The electrolyte was allowed to stand and react for 12 h at 25°C. The LiF was then separated by centrifugation, dried, and pressed into sheets for electronic conductivity testing. The resulting electronic conductivity graph is shown below. Figure 16 As shown, by Figure 16 It can be seen that the electronic conductivity of LiF after modulation by 3,4,5-TTFPB is 8.437 × 10⁻⁶. -9 S cm -1 It remains at 10 -9 S cm -1 The magnitude indicates that grain refinement did not lead to significant electronic conduction in LiF. Therefore, this system improves the conductivity of LiF. + While maintaining transmission capability, it can still maintain the good electronic insulation properties of LiF.
[0068] The lithium battery electrolyte obtained in Example 5 was used in a Li-Gr half-cell. After standing for 8 hours, it was activated at 0.1 C for 3 cycles. Then, the cycle performance of the half-cell under 1C conditions was tested, and the obtained cycle performance graph is shown in the figure. Figure 17 As shown, from Figure 17 It can be seen that the battery containing 3,4,5-TTFPB electrolyte exhibits better capacity retention after long cycling. After about 250 cycles, its capacity decay is significantly slower than that of the comparative example 1, and it still maintains 315 mAh g⁻¹ after 500 cycles. -1 Comparative Example 1 is 260 mAh g -1 The coulombic efficiency remained close to 100% during cycling. This indicates that the small-sized LiF formed by 3,4,5-TTFPB regulation can reduce interfacial transport resistance and improve long-term cycling stability.
[0069] The lithium battery electrolyte obtained in Example 5 was used in a Li-Gr half-cell. After standing for 8 hours, it was activated at 0.1 C for 3 cycles. Then, the rate performance of the half-cell was tested, and the rate performance graph is shown in the figure. Figure 18 As shown, from Figure 18It can be seen that the 3,4,5-TTFPB system maintains a high discharge specific capacity in the range of 0.1–2C, and is approximately 345 mAh g⁻¹ at 1C and 2C. -1 and 310mAh g -1 The electrolyte concentration was significantly higher than that of Comparative Example 1; it could still maintain approximately 160 mAh g at 5C. -1 The electrolyte in Comparative Example 1 was only about 60 mAh g. -1 After the rate of change is restored to 0.1C, the capacity recovers to approximately 365 mAh g. -1 This indicates that it has good rate reversibility and interfacial dynamics performance.
[0070] As can be seen from the test data in Example 5, 3,4,5-TTFPB can also refine LiF to the nanoscale, increasing its ionic conductivity to 10. -6 S cm -1 The XRD peak broadening and electrochemical performance improvement are slightly different from those of 2,4,6-TTFPB, indicating that the steric hindrance environment formed by different fluorine substitution sites further affects the recrystallization of LiF and the final grain size.
[0071] Example 6: The method for controlling the growth of alkali metal fluoride crystals at the solid electrolyte interface in this example involves adding a boron-containing additive, triphenylborane (TPB), to a lithium battery electrolyte containing components capable of forming LiF. Details are as follows:
[0072] 1. Mix ethylene carbonate (EC): ethyl methyl carbonate (EMC): dimethyl carbonate (DMC) in a volume ratio of 1:1:1 to obtain a mixed solvent; then add LiPF6 to the mixed solvent at a concentration of 1 M, stir and mix thoroughly to obtain the basic electrolyte.
[0073] 2. Add 1% (by volume) of triphenylborane (TPB) to the base electrolyte and mix until a homogeneous solution is formed to obtain the lithium battery electrolyte.
[0074] To verify the direct size regulation effect of TPB on LiF crystals, 0.5 mmol of pristine LiF with a particle size of 1-2 μm was added to 2 mL of the TPB-containing lithium battery electrolyte obtained in Example 6, and the mixture was allowed to stand and react at 25°C for 12 h. After the reaction, the LiF solid was separated, and its morphology was characterized by SEM and TEM. TPB has a triarylborane skeleton but the aromatic ring does not contain fluorine substituents, and can be used as a structural reference under different steric hindrance environments. TPB exerts an attack and solubilization effect on LiF through the boron-containing center, and its occupancy of the molecular periphery space is different from that of fluorine-substituted triarylboranes, thereby producing different degrees of LiF size regulation effect. Figure 19 As shown, after 12 h of TPB treatment, the original LiF crystals were refined from micron-sized bulk crystals into numerous smaller, regular particles, mostly cubic or near-cubic in shape, with LiF crystal sizes of approximately 90–100 nm. Compared to the 2,4,6-TTFPB and 3,4,5-TTFPB systems, the particles treated with TPB exhibited more complete crystal shapes and relatively larger sizes, indicating that its effect on limiting further grain growth and particle aggregation after LiF recrystallization was relatively weak. Figure 20 The TEM images of the LiF samples show that the TPB-treated LiF mainly consists of well-defined square or near-cubic nanocrystals with some degree of particle aggregation. This result is consistent with the SEM results, indicating that TPB can significantly refine the original LiF, while the resulting particles still maintain a relatively complete crystal shape.
[0075] The XRD pattern of the LiF sample obtained after reacting the original LiF in the TPB-containing electrolyte of Example 6 for 12 h is shown below. Figure 21 As shown, from Figure 21 It can be seen that the TPB-treated sample exhibits characteristic diffraction peaks of LiF at approximately 38°, 44°, 66°, 79°, and 83°, without any obvious new phase. Compared with Comparative Example 1, the peak intensity decreased and broadened to some extent, but the diffraction peaks remained relatively sharp, indicating that TPB can reduce the LiF grain size while maintaining a high degree of crystallinity. This result is consistent with the relatively intact cubic nanocrystal phase observed in SEM and TEM.
[0076] 0.5 mmol of pristine LiF with a particle size of 1-2 μm was added to 2 mL of the TPB-containing lithium battery electrolyte obtained in Example 6. The mixture was allowed to stand and react at 25°C for 12 h. The LiF was then separated by centrifugation, dried, and pressed into sheets for ionic conductivity testing. The resulting ionic conductivity test graph is shown below. Figure 22 As shown, from Figure 22 It can be seen that the ionic conductivity of LiF after TPB regulation is 6.91 × 10⁻⁶. -8 S cm -1Compared to the original LiF's 5.95 × 10⁻⁶, -11 S cm -1 The improvement was approximately three orders of magnitude, but still lower than that achieved with 2,4,6-TTFPB and 3,4,5-TTFPB-modified LiF. Combining morphology and XRD results, it is evident that while TPB can refine LiF and improve ion transport, its relatively large grain size limits its ability to enhance ion conductivity.
[0077] 0.5 mmol of pristine LiF with a particle size of 1-2 μm was added to 2 mL of the TPB-containing lithium battery electrolyte obtained in Example 6. The mixture was allowed to stand and react at 25°C for 12 h. The LiF was then separated by centrifugation, dried, and pressed into sheets for electronic conductivity testing. The resulting electronic conductivity graph is shown below. Figure 23 As shown, by Figure 23 It can be seen that the electronic conductivity of LiF after TPB modulation is 5.304 × 10⁻⁶. -9 S cm -1 It remains at 10 -9 S cm -1 The electronic insulation level is on the order of magnitude higher. This indicates that after TPB modulates the size of LiF crystals, it can improve ion transport capability while still maintaining the effective barrier of LiF to electron transport.
[0078] The lithium battery electrolyte obtained in Example 6 was used in a Li-Gr half-cell. After standing for 8 hours, it was activated at 0.1 C for 3 cycles. Then, the cycle performance of the half-cell under 1C conditions was tested, and the obtained cycle performance graph is shown in the figure. Figure 24 As shown, from Figure 24 It can be seen that under 1C cycling conditions, the TPB system of Example 6 initially exhibits a capacity close to that of the uncontrolled Comparative Example 1, but shows a slower capacity decay after approximately 250 cycles, and still maintains 305 mAh g⁻¹ after 500 cycles. -1 The comparative example 1 decreased to approximately 260 mAh g. -1 The coulombic efficiency remained close to 100% during the cycle. This indicates that smaller LiF particles regulated by TPB can still improve the long-term stability of the interface, but the improvement is less than that of the system with more significant particle size refinement.
[0079] The lithium battery electrolyte obtained in Example 6 was used in a Li-Gr half-cell. After standing for 8 hours, it was activated at 0.1 C for 3 cycles. Then, the rate performance of the half-cell was tested, and the rate performance graph is shown in the figure. Figure 25 As shown, from Figure 25 It is evident that the TPB system has a capacity close to that of the uncontrolled comparative example 1 at 0.1C, and its advantage gradually becomes apparent as the rate of increase, maintaining approximately 315 mAh g⁻¹ at both 1C and 2C. -1 and 250 mAh g -1It can still maintain approximately 110 mAh g at 5C. -1 All were higher than the control group 1; after recovering to 0.1C, the capacity returned to approximately 360 mAh g. -1 This indicates that TPB can improve interfacial kinetics by regulating the size of LiF, but the improvement at high rates is weaker than that of the 2,4,6-TTFPB and 3,4,5-TTFPB systems.
[0080] The test results from Example 6 show that TPB can refine the original micron-sized LiF into regular nanocrystals, reducing the ionic conductivity from 10... -11 S cm -1 Increased to 10 -8 S cm -1 Order of magnitude, while maintaining 10 -9 S cm -1 The additive exhibits orders-of-magnitude lower electronic conductivity and improved cycling and rate performance. Compared to the two trifluorosubstituted triarylboranes, the LiF particles obtained by TPB are relatively larger, with sharper XRD peaks, but the improvement in ionic conductivity and high-rate performance is relatively limited, further demonstrating that the steric environment of the additive plays an important regulatory role in the crystal size and interfacial properties of LiF.
[0081] This invention utilizes a boron-containing additive to regulate the growth of alkali metal fluoride crystals at the solid electrolyte interface. The core of this method involves adding a boron-containing crystallization regulator that strongly interacts with fluorine (F) to the base electrolyte, and then having this additive participate in the formation and evolution of LiF crystals during battery formation and subsequent cycling. The base electrolyte contains fluorine-containing components capable of forming LiF at the negative electrode interface, and the boron-containing additive is dispersed or dissolved in the base electrolyte as an electrolyte additive. Through the Lewis acid properties of the boron-containing additive and its affinity for fluorine (F), a stable interaction occurs between the boron centers and the fluorine on the LiF surface, resulting in an aggressive solubilizing effect on LiF. This promotes the surface dissolution, local fragmentation, and recrystallization of existing or forming LiF. Simultaneously, the steric environment created by different additive molecules regulates the process of the additive approaching the LiF surface and the recrystallization, aggregation, and continued growth of LiF particles, thereby obtaining LiF crystals of different sizes and dispersion states. Through the regulation of the boron-containing additive, LiF is refined into regular nanocrystals, thereby improving the rate performance of the battery.
Claims
1. A method for regulating the growth of alkali metal fluoride crystals at a solid electrolyte interface, characterized in that, The method involves adding a boron-containing additive to a lithium battery electrolyte containing a LiF-forming component; wherein the boron-containing additive is one or more of tris(2,4,6-trifluorophenyl)borane, tris(3,4,5-trifluorophenyl)borane, and triphenylborane.
2. The method for regulating the growth of alkali metal fluoride crystals at a solid electrolyte interface according to claim 1, characterized in that, The amount of boron-containing additive added is 0.5% to 1.5% of the volume of the lithium battery electrolyte containing the LiF component.
3. A method for regulating the growth of alkali metal fluoride crystals at a solid electrolyte interface according to claim 1 or 2, characterized in that, The amount of boron-containing additive added is 1% of the volume of the lithium battery electrolyte containing the LiF component.
4. A method for regulating the growth of alkali metal fluoride crystals at a solid electrolyte interface according to claim 1 or 2, characterized in that, Lithium-ion battery electrolytes that can form LiF components are electrolytes containing LiPF6, LiFSI, or LiTFSI.
5. A method for regulating the growth of alkali metal fluoride crystals at a solid electrolyte interface according to claim 1 or 2, characterized in that, The lithium battery electrolyte that can form LiF components is formed by adding LiPF6 to a mixed solvent at a concentration of 1 M; wherein the mixed solvent is obtained by mixing ethylene carbonate, methyl ethyl carbonate and dimethyl carbonate evenly at a volume ratio of ethylene carbonate: methyl ethyl carbonate: dimethyl carbonate of 1:1:1.